Faktor Predisposisi dengan Praktik Personal Hygiene Pedagang Makanan Kaki Lima di Kotamara Kota Baubau - Eky Endriana Amiruddin, Taswin, Dahmar, Ayu Rahmalia Putri (Kampurui Jurnal Kesehatan Masyarakat, 2021)
The results of observations made in Kotamara that food vendors are still found, take food that is served to customers by hand so they do not pay attention to aspects of personal hygiene. This is due to the lack of knowledge, attitude and length of work of street vendors in Kotamara in the practice of personal hygiene in serving the food they sell. The purpose of this study was to determine the relationship between predisposing factors and personal hygiene practices in street food vendors in Kotamara, Baubau City. This type of research is an analytic observational approach with a cross sectional study design. The population in this study were all street food vendors in Kotamara with 67 traders. The sampling technique using total sampling, which is as many as 67 respondents. The data analysis used is univariate analysis and biveriat analysis. The results of the study based on statistical tests based on the relationship of the independent variable with the dependent variable obtained length of effort with a value of p value = 0.010 less than α = 0.05. knowledge with p value = 0.001 smaller than α = 0.05 and attitude p value = 0.001 smaller than α = 0.05. The conclusion of this study, there is a significant relationship between predisposing factors between the length of effort, knowledge and attitude with the personal hygiene practices of street food vendors in Kotamara, Baubau City. Suggestions in this study, namely conducting training or counseling on food traders in order to increase knowledge, attitudes and actions so that what is done by food vendors in line and have a positive impact in food processing.